Wellington Koo China - Clements, Jonathan 1971- (Haus histories, 2008)
Wellington Koo achieved notoriety at the Paris Peace Conference for sternly resisting Japanese attempts to hold onto seized German colonial territory in mainland China. In protest, the Chinese were the only dele gates not to sign the subsequent Treaty of Versailles. Koo was later a founding member of the United Nations.